Reduced density of glutamine synthetase immunoreactive astrocytes in different cortical areas in major depression but not in bipolar I disorder - Bernstein, Hans-Gert; Meyer-Lotz, Gabriela; Dobrowolny, Henrik; Bannier, Jana; Steiner, Johann; Walter, Martin; Bogerts, Bernhard (Frontiers in Cellular Neuroscience, 2015)
There is increasing evidence for disturbances within the glutamate system in patients with affective disorders, which involve disruptions of the glutamate-glutamine- cycle. The mainly astroglia-located enzyme glutamine synthetase catalyzes the ATP-dependent condensation of ammonia and glutamate to form glutamine, thus playing a central role in glutamate and glutamine homoeostasis. However, glutamine synthetase is also expressed in numerous oligodendrocytes, another class of glial cells implicated in mood disorder pathology. To learn more about the role of glia-associated glutamine synthetase in mental illnesses, we decided to find out if numerical densities of glial cells immunostained for the enzyme protein differ between subjects with major depressive disorder, bipolar disorder and psychically healthy control cases. Counting of glutamine synthetase expressing astrocytes and oligodendrocytes in eight cortical and two subcortical brain regions of subjects with mood disorder (N=14), bipolar disorder (N=15) and controls (N=16) revealed that in major depression the densities of astrocytes were significantly reduced in some cortical but not subcortical gray matter areas, whereas no changes were found for oligodendrocytes. In bipolar disorder no alterations of glutamine synthetase-immunoreactive glia were found. From our findings we conclude that (1) glutamine synthetase expressing astrocytes are prominently involved in glutamate-related disturbances in major depression, but not in bipolar disorder and (2) glutamine synthetase expressing oligodendrocytes, though being present in significant numbers in prefrontal cortical areas, play a minor (if any) role in mood disorder pathology. The latter assumption is supported by findings of others showing that - at least in the mouse brain cortex - glutamine synthetase immunoreactive oligodendroglial cells are unable to contribute to the glutamate-glutamine cycle due to the complete lack of amino acid transporters (Takasaki et al.